Effect of magnetite on physical, tribological and magnetic characteristics of kenaf fibre - Pujari, Satish; Kumar, Sattaru Santosh; S. Naveen, Nambala; Devi, Chinta Neelima; Subramonian, Sivarao (ICE Publishing, 2023)
The demand for organic fibres with remarkable mechanical, magnetic and physical properties is rising. As a result, the current study investigated the impact of magnetite reinforcement on kenaf fibre. The test samples were prepared by using the hand lay-up process with the addition of magnetite in the range 10–40 wt%. The test results showed that samples with a 30% magnetite content had the best mechanical, physical and tribological characteristics. They showed water absorption of 0 g, average wear of 112 mm and an average frictional force of 1.1 N. The magnetic absorption values of samples with 30 and 40 wt% magnetite were −0.0003 78 to 0.0003 8623 and −0.0002 6021 8 to 0.0002 5781 4 emu/g, respectivel